PENDIDIKAN MORAL DAN KARAKTER: SEBUAH PANDUAN - Taher, Andi (Analisis: Jurnal Studi Keislaman, 2014)
MORAL EDUCATION AND CHARACTER BUILDING : A HANDBOOK: Education Institutions have a very important task associated with moral and character development. Unfortunately, the  various activities  in schools are not enough to support  the implementation of moral education.  This book may become the main handbook for moral and character education in schools as it contains a very strong philosophical foundation  accompanied by the clear strategies and techniques of implementation. Other than to support the activities  in the classroom, this book also offers a detail  and applicable  formula of moral and character  education outside the classroom, including efforts to develop character through sports activities